2015
DOI: 10.1021/acs.nanolett.5b04003
|View full text |Cite|
|
Sign up to set email alerts
|

“Freeing” Graphene from Its Substrate: Observing Intrinsic Velocity Saturation with Rapid Electrical Pulsing

Abstract: Rapid (nanosecond-scale) electrical pulsing is used to study drift-velocity saturation in graphene field-effect devices. In these experiments, high-field pulses are utilized to drive graphene's carriers on time scales much faster than that on which energy loss to the underlying substrate can occur, thereby allowing the observation of the highest saturation velocities reported to date. In a dramatic departure from the behavior exhibited by conventional metals and semiconductors, as the electron or hole density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 52 publications
4
72
2
Order By: Relevance
“…This effect can be considered a solid-state analog of the Schwinger effect [23][24][25][26] . However, the main consequence from the theory on the current-voltage relation, I ∼ V α with the exponent α greater than 1, has been inconsistent with majority of the measured dc transport in graphene 6,8,27 where the current saturation gradually crosses over to a linear or marginally sublinear I-V relation (α ≈ 1).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This effect can be considered a solid-state analog of the Schwinger effect [23][24][25][26] . However, the main consequence from the theory on the current-voltage relation, I ∼ V α with the exponent α greater than 1, has been inconsistent with majority of the measured dc transport in graphene 6,8,27 where the current saturation gradually crosses over to a linear or marginally sublinear I-V relation (α ≈ 1).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, the phenomena of current saturation have attracted intense interest. 7,8,10,11,36 It is found that the current saturation in graphene at high electric field depends on the optical phonon frequency ω ph and equilibrium current carrier density n eq . The former is a parameter independent of electric control, and the latter is controlled through the chemical potential µ.…”
Section: B Steady-state Current At Large Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key result we demonstrate is significant immunity of transistor action to hot-carrier trapping, providing a marked improvement over graphene-on-SiO 2 devices, whose operation is known to be negatively impacted by such trapping at high fields. 1723 We also identify the dynamics of self-heating in the graphene/h-BN devices and discuss how this influences transistor performance. Overall, our results establish the excellent immunity of the graphene/h-BN system to hot-carrier degradation and highlight its value as a specific materials combination for the realization of active devices.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Therefore, the answer to a question like how the substrate will impact the carrier saturation velocity of a 2D material is unlikely to be unique. [9][10][11] Furthermore, it is unclear how thermal annealing or unintended thermal stress during temperature dependent measurements will affect the material properties, and how will be the interplays of above mentioned "intrinsic" (substrate) and extrinsic perturbations responding to the annealing.…”
Section: Introductionmentioning
confidence: 99%